Effect of alloy element on microstructure and properties of heat-affected zone. Issue 15 (13th October 2022) - Bian, Shouyuan; Zhao, Heming; Wang, Jiaji; Li, Weijuan; Wang, Chuan; Pang, Qihang; Zhang, Youjian; Guo, Jing
ABSTRACT: In the present study, the influences of general composition (GC steel), magnesium deoxidation treatment (MT steel) and magnesium deoxidation treatment with high vanadium (MVT steel) content on the inclusions, microstructure and low-temperature toughness of the welding heat affected zone of EH36 steel were studied. The thermal cycle process of the heat-affected zone (HAZ) was simulated by a thermal simulator, and then microstructure and impact properties were tested and analyzed. Obtained results show that Magnesium deoxidation treatment and magnesium deoxidation treatment with higher vanadium content decrease the number and average size of inclusions. Compared with GC steel, the austenite grain size of MT and MVT steel reduces at high temperatures so that the nucleation temperature of acicular ferrite in HAZ microstructure increases. Compared with GC steel, the low-temperature impact toughness of HAZ by MT steel and MVT steel increases.